(untitled) (The Macau Ricci Institute Journal, 2022)
With the outbreak of the Covid-19 pandemic, we find ourselves living in a time of crisis. Our cultural and technological developments are being largely challenged. The pandemic tells us that the ultimate solution for all the problems we face is not in our own hands. God is where we find the final hope and salvation. In this regard, the present crisis may not be totally negative for our lives. To read the situation positively and even spiritually, we turn to the 4th-century Church Father Gregory of Nyssa, who is famous for his apophatic Mysticism. Viewing through the apophatic lens, the crisis has reminded us of the limitations of human intellectual power, which may turn our eyes to the final cause of the world, the ultimate meaning of life, and eventually what is essential for our final salvation. That is where we start our spiritual transformation anew. Key Words Spiritual transformation, Gregory of Nyssa, apophatic awakening